Memastikan Pemenuhan Hak-Hak Pendidikan Warga Negara Melalui Penyelenggaraan PPDB Yang Obyektif, Transparan, Dan Akuntabel - Asep Suryana (BADAN PENERBIT STIEPARI PRESS, 2024)
PPDB is an important instrument in fulfilling the right to education, but its implementation is often colored by various problems such as non-objectivity, non-transparency, and unaccountability. This study analyzes the implementation of PPDB in 2024 to identify problems and formulate recommendations for improvement. The purpose of this study is to analyze the implementation of PPDB in 2024 in West Java, identify emerging problems, and formulate recommendations for policy improvement to improve the objectivity, transparency, and accountability of PPDB. Research Methods This study uses a qualitative descriptive method by collecting data through mentoring, surveys, and observations of the implementation of PPDB in West Java. The results of the study show that despite improvements, the implementation of PPDB in 2024 in West Java is still far from ideal. Some of the problems found include: Unobjectivity: Late determination of technical instructions, inaccuracy of capacity data, and weak coordination of the committee. Non-transparency: Lack of technical socialization, lack of open complaint handling, and limited public monitoring space in the online PPDB application. Unaccountability: Lack of monitoring, reflection, evaluation, and preparation of reports. Based on the results of the research, there are several recommendations that need to be implemented in the implementation of the upcoming PPDB, including: local governments need to be more active in coordinating with Pusdatin to compile accurate graduate projection data and capacity.